miR-145 regulates chemoresistance in hepatocellular carcinoma via epithelial mesenchymal transition - Ju, B-L; Chen, Y-B; Zhang, W-Y; Yu, C-H; Zhu, D-Q; Jin, J (Cellular and Molecular Biology, 2015)
Resistance to chemotherapeutic drugs is a major obstacle in hepatocellular carcinoma (HCC) therapy. MicroRNA-145 (miR-145) has been shown to be down-regulated in several cancers and may be involved in the process of carcinogenesis. The present study aimed to evaluate the effects of miR-145 in adriamycin (ADM)-resistant human HCC cells. We found that miR-145 was significantly reduced in HepG2/ADM and HuH7/ADM cells compared with the chemosensitive parental cells. Up-regulation of miR-145 increased the ADM cytotoxicity in chemoresistant tumor cells. In addition, Smad3 was identiï¬ed as the target of miR-145 and miR-145 overexpression inhibited Smad3 expression both at the mRNA and protein levels. The luciferase reporter assay confirmed that Smad3 was a direct target of miR-145. Moreover, up-regulation of miR-145 suppressed Smad3 related EMT features as shown by increased expression of E-cadherin and reduced vimentin level in HepG2/ADM and HuH7/ADM cells. Our study demonstrated that miR-145 modulated both chemoresistance and EMT in HCC cells, and up-regulation of miR-145 might be a potential therapeutic strategy for treatment of chemoresistant HCC.